The mediating role of sleep quality in the association between urinary incontinence and depressive symptoms: A study with older Korean Americans Living in Subsidized Senior Housing - Seo-Yun Choi; Ju Hyun Kim; Soondool Chung; Yuri Jang (PLoS ONE, 2026)
Urinary incontinence (UI) is a prevalent health issue among older adults. Depressive symptoms often accompany UI; however, the pathways linking these conditions remain understudied. In this study, we conceptualized sleep quality as a potential mediator in the association between UI and depressive symptoms. The mental health burden of UI is anticipated to be indirectly associated with impaired sleep quality. The mediating role of sleep quality was tested in a sample of 306 older Korean Americans living in low-income senior housing (mean age = 79.4 years, range = 65–102). Regression analyses showed a significant association between UI and depressive symptoms. Mediation analysis using the Hayes PROCESS macro showed that the indirect effect of UI on depressive symptoms through sleep quality was significant (B [SE] = 0.59 [0.21], bias-corrected 95% CI = [0.20, 1.02]), accounting for approximately 24% of the total effect. The findings suggest that compromised sleep quality may serve as a potential pathway linking UI and depressive symptoms. Sleep quality should be addressed in efforts to promote the mental health of older adults experiencing UI.